AMEROSÉIDOS ASOCIADOS A NIDOS DE NEOTOMA MEXICANA BAIRD, 1855 (RODENTIA: MURIDAE) Y DESCRIPCIÓN DE UNA NUEVA ESPECIE DEL GÉNERO SERTITYMPANUM ELSEN Y WHITHAKER, 1985 - Villegas-Guzmán, Gabriel A.; Montiel-Parra, Griselda; Vargas, Margarita; Polaco, Oscar J. (Instituto de Ecología, A.C., 2004)
The first record of three ameroseid mites species, Kleemannia plumigera, Ameroseius sp., and Sertitympanum sp. nov., inhabiting a nest of Neotoma mexicana from the state of Durango, México is documented. The distribution of mites within the nest components are characterized. The new species in the genus Sertitympanum is described.